PENGAMALAN NORMA-NORMA AGAMA DALAM BENTUK KEGIATAN KEAGAMAAN DI KECAMATAN PADANGSIDIMPUAN UTARA KOTA PADANGSIDIPUAN - ALI AMRAN (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2017)
Low application of religious activities of the societies were the main problems of this research. It is also seen in the major muslim societies, they did not apply the muslim attitudes based on Islamic teaching. Many of them did not do Islamic activities asked by Islam, such as did not do shalat at the time, and Islamic norms are still increased. This research was qualitative research to show the religious norms in doing praying together and in joining the Islamic preachings. It is shown that the Muslim societies still have low performance in doing together praying and joing preaching in the Mosques in North Padangsidimpuan. It is caused of some reasons, such as religious awareness, economic sides, having busy in working, and the weakness of Islamic knowledge and faith